Penerapan Restoratif Justice Terhadap Pelaku Tindak Pidana Penganiayaan Anak - Benony Gardjalay; Hadibah Zachra Wadjo; Yeheskel Wessy (LUTUR Law Journal, 2022)
In accordance with the problems mentioned earlier, this research is a normative study of the application of restorative justice to perpetrators of criminal acts of child abuse through a conceptual approach, a statutory approach, prioritizing the use of legal materials through normative and empirical studies and various findings regarding the application of restorative justice against Perpetrators of Crime of Child Abuse, then from the results of this description conclusions and suggestions can be drawn. The results of the research and analysis use the concept of legal protection, which is an initial framework for thinking about the implementation of restorative justice for perpetrators of child abuse crimes. The results of the study show that the perpetrators and/or suspects of child abuse can be submitted to restorative justice by fulfilling various formal requirements for the victim by involving the families of both parties and related elements in society, namely resolving problems amicably by prioritizing applicable customary law and binding for the purpose of terminating an investigation based on restorative justice.